1995
DOI: 10.1007/bf00571512
|View full text |Cite
|
Sign up to set email alerts
|

Desmin myopathy with cardiomyopathy

Abstract: We report a case of abnormal desmin accumulation within the muscle of a 30-year-old female with a 2-year history of cardiomyopathy and axial muscle weakness. Serum creatine kinase was normal. A quadriceps muscle biopsy revealed pink hyaline inclusions, which stained for acid phosphatase and with PAS and were present in both fibre types. Electron microscopy showed these inclusions to consist of aggregates of irregularly arranged 6- to 15-nm-diameter filaments enmeshed within a central core of dense granulo-amor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1999
1999
2003
2003

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…89 Filaments (15-18 nm) may be present in association with rimmed vacuoles. 4,24,38,41 Some investigators 94 have found smaller, 8-10-nm filaments, but these could not be found by others, 89 despite intensive searching. On immunohistochemical analysis, the nonhyaline lesions react to desmin, dystrophin, neural cell adhesion molecule, gelsolin, and ␤-amyloid precursor protein.…”
Section: 76mentioning
confidence: 89%
See 1 more Smart Citation
“…89 Filaments (15-18 nm) may be present in association with rimmed vacuoles. 4,24,38,41 Some investigators 94 have found smaller, 8-10-nm filaments, but these could not be found by others, 89 despite intensive searching. On immunohistochemical analysis, the nonhyaline lesions react to desmin, dystrophin, neural cell adhesion molecule, gelsolin, and ␤-amyloid precursor protein.…”
Section: 76mentioning
confidence: 89%
“…28,40 Desmin is not the only muscle protein that accumulates in this myopathy, and, therefore, the term "myofibrillar myopathy" has been proposed. 89 In fact, this entity has been reported under a variety of names: desmin myopathy, 24 desmin storage myopathy, 35 spheroid body myopathy, 41 cytoplasmic body myopathy, 25 Mallory body myopathy, 38 intermediate filament myopathy, 38 familial cardiomyopathy with subsarcolemmal vermiform deposits, 23 and myopathy with intrasarcoplasmic accumulation of dense granulofilamentous material. 34 It is likely that patients who have been diagnosed with other forms of distal myopathy actually have myofibrillar myopathy.…”
Section: Myofibrillar Myopathy With Abnormal Foci Ofmentioning
confidence: 97%
“…A large number of sporadic cases of cardiac and skeletal myopathy with intracytoplasmic desmin deposits in the muscle cells have been reported [21–25], but the causal relationship between the sporadic and familial cases has not been addressed. The present study provides evidence that a de novo mutation in the desmin gene is responsible for sporadic desmin myopathy.…”
Section: Discussionmentioning
confidence: 99%
“…48 The respective inclusions are associated with aggregation of desmin. 70, 148 This has resulted in the terms desmin‐related myopathies, 67, 74 myopathies associated with desmin storage, 26, 91 or desminopathies. 71 Clinically, these desmin‐related myopathies have been seen in children 15, 25, 48, 54, 55, 154, 195 and adults.…”
Section: Congenital Myopathies With Mutant Proteinsmentioning
confidence: 99%
“…30, 54, 55, 97 Rigid spine 158 as well as asymptomatic familial hyperCKemia 155 have been observed within the spectrum of these myopathies. When the morphological findings consisted of granulofilamentous material, cardiomyopathy was a regularly associated clinical feature, 26, 48, 65, 191 with granulofilamentous material and desmin deposits 7, 181 also present in cardiac myocytes. 118 Peripheral neuropathy marked by giant axons, owing to accumulation of neurofilaments, was seen in some patients 15, 117, 162 and suggests a wide heterogeneous clinical spectrum among the desmin‐related myopathies.…”
Section: Congenital Myopathies With Mutant Proteinsmentioning
confidence: 99%